ANALISIS FAKTOR-FAKTOR PERSEPSI PEGAWAI MENGENAI PENGGELAPAN PAJAK (STUDI KASUS PADA BALAI PEMERINTAHAN DESA DI DIY) (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to analyze and get empirical evidence on employee perceptions about the government of the special region of Yogyakarta Village regarding the effect of the taxation system, protection against tax incorporation. This research is a quantitative study and the population is all employees who are within the scope of the Yogyakarta Special Region Government Village. For sample selection is to use a saturated sample that obtained as many as 86 respondents to be studied. In collecting data using a questionnaire method and for data analysis using the SPSS program. The results of this study indicate that the variables of justice and discrimination affect tax evasion. The taxation system variable has no effect on tax evasion.
Keywords: Justice; Taxation System; Discrimination; Tax Evasion